The struggle against the shadow economy and corruption: the possibilities of accounting and digital technologies - Semaniuk, Vita; Kuchciak, Iwa (Journal of Finance and Financial Law, 2025)
The purpose of the article. The shadow economy and corruption pose significant threats to national economies, as illicit income from financial crimes and tax evasion often funds organized crime and terrorism, while exacerbating inequality and hindering development. This article examines key categories of financial crime, including asset misappropriation, fraud, bribery, cybercrime, and accounting violations. The study aims to enhance accounting methodology as a tool in combating corruption and the shadow economy. The central hypothesis is that improvements in accounting and auditingwhen supported by ethical, organizational, and technological infrastructurecan reduce these phenomena. Accounting information, when integrated with digital systems and ethical standards, becomes a powerful instrument for transparency and accountability. Methodology. The study’s methodological approach integrates theoretical and empirical components to examine the role of accounting in combating corruption and the shadow economy. Theoretically, it draws on general philosophical and scientific methods, including bibliometric analysis, synthesis, and historical-logical approaches, to explore the structural roots of financial crime and the potential of accounting for transparency and control. Empirically, the research involved 15 semi-structured interviews with accounting professionalsboth accountants and auditors from public and private sectors. Results of the research. The interviews aimed to identify practical challenges in financial transparency, ethical dilemmas, and the impact of digitalization on fraud prevention. This qualitative data enriched the study’s conclusions, offering a multidimensional perspective on how accounting practices are shaped by real-world constraints, organizational culture, and technological readiness.